Parents’ Perception of the Online Delivery of Instruction in the Primary Level - Cherrylyn S. Cacharro; Kim Justine Abretil; Emely Obeja; Ermie Ann Esquierda; Melissa Profetana; Honeylette Cabriana; Alma Sonia Sanchez-Danday; Billy A. Danday (PT FORMOSA CENDEKIA GLOBAL, 2023)
Parents play a huge part in how a child learns. This study examined parents' perception of online instruction at the primary grade level and its relationship to their demographic profile. The study employed a descriptive-correlational research design using a five-point Likert scale questionnaire. A total of 80 parents of primary-level pupils were chosen as respondents. Parents' demographic profiles and perceptions were described using frequency counts, minima, maxima, means, and percentages. Point-biserial correlations and Spearman-Rho correlations were used to determine the variables' significant relationships. The data showed a significant relationship between the parent's employment status and their perception of online delivery of instruction in terms of the learning management system. At the same time, other dimensions were revealed to be non-significant to the parents' demographic profile. The study found that most parents adhered to the fact that online delivery of instruction offers flexible education and provides personalized learning experiences where pupils can learn independently.